Morphometry of Dry Sub Axial Vertebra: A Nepalese Study - Dhakal, Arun; Adhikari, P; Ranjit, N; Budhathoki, D (Nepal Medical College Journal, 2021)
There is paucity in literature describing the morphology of sub-axial vertebra of the local population. Available studies are limited to the body, intervertebral disk, spinal canal and Torg’s ratio of the cervical vertebra. Therefore, the present study aims to document various morphological parameters of sub axial vertebra. Sixty-four dry sub-axial vertebrae of the Nepalese population were studied using Vernier Calipers calibrated to 0.1 mm accuracy. Paired parameters of pedicle, lamina, uncinate process, the distance of the apex of the uncinate process to intervertebral foramen and foramen transversarium were measured. Similarly, unpaired parameters including spinous process length, vertebral foramen anteroposterior width, vertebral foramen transverse diameter and Torg’s ratio were evaluated. Except the height of left lamina of C3 to C6 vertebrae, none of the parameters showed significant side differences. Significant higher values of C7 were noted against C3-C6 on vertebral body height, vertebral body anteroposterior diameter, spinous process length and vertebral foramen anteroposterior diameter. Population data of sub-axial vertebra available in literature showed mixed results with ours. Interestingly, our observations either compared to (lamina, uncinate process, anteroposterior diameter of spinal canal and Torg’s ratio) or were larger (Pedicle and spinous process) than the Indian study with pedicle axis length being largest among all the compared studies. The information of this study may be used as a reference database for our local setting and could be of value in preoperative planning and in designing implants.